Is IL-1β Further Evidence for the Role of Propionibacterium acnes in Degenerative Disc Disease? Lessons From the Study of the Inflammatory Skin Condition Acne Vulgaris - Slaby, Ondrej; McDowell, Andrew; Brüggemann, Holger; Raz, Assaf; Demir-Deviren, Sibel; Freemont, Tony; Lambert, Peter; Capoor, Manu N. (Frontiers in Cellular and Infection Microbiology, 2018)
The pathogenesis of degenerative disc disease is a complex and multifactorial process in which genetics, mechanical trauma, altered loading and nutrition present significant etiological factors. Infection of the intervertebral disc with the anaerobic bacterium Propionibacterium acnes is now also emerging as a potentially new etiological factor. This human commensal bacterium is well known for its long association with the inflammatory skin condition acne vulgaris. A key component of inflammatory responses to P. acnes in acne appears to be interleukin (IL)-1β. Similarly, in degenerative disc disease (DDD) there is compelling evidence for the fundamental roles of IL-1β in its pathology. We therefore propose that P. acnes involvement in DDD is biologically very plausible, and that IL-1β is the key inflammatory mechanism driving the host response to P. acnes infection. Since there is a solid theoretical basis for this phenomenon, we further propose that the relationship between P. acnes infection and DDD is causal.